Smart furniture design, innovations, and challenges in the digital age (Al-Academy, 2026)
Smart furniture can be considered part of the smart home and smart city, overlapping with the furniture sector and the Internet of Things. All of these terms are also linked to the phenomenon of Industry 4.0, maximizing benefits through synergies that produce ambient intelligence while creating a holistic home. Furniture is a key component of our homes, transforming old, unsmart spaces into smart spaces, providing location and contextual services, navigation services, personalized services, and ubiquitous internet connectivity. The importance of this research lies in its keeping pace with recent developments in smart furniture design, making it useful for researchers and designers in this field. This research contributes to improving quality of life by understanding the impact of technology on user comfort, safety, and energy efficiency. It also promotes innovation in the industry by providing practical examples and case studies from leading companies, which helps develop new smart furniture solutions. It also supports the concept of sustainability by discussing how smart furniture can be made more environmentally friendly and energy efficient